The Influence of Financial Resource Scarcity on Consumer Lifestyles - Nyman, Jannica; Piha, Samuel (Belgium, 2026)
Due to recent geopolitical disruptions, many countries that once enjoyed steady improvements in well-being are now facing economic stagnation and even the threat of permanent societal decline. This study examines these macroeconomic trends from the perspective of middle class consumers, focusing on how crisis-induced financial resource scarcity influences their lifestyles. Building on recent literature on resource scarcity, we propose an initial framework for analyzing coping strategies that consumers adopt to alter their lifestyles and behaviors in response to resource scarcity. We detail our planned methodology, which includes interviews with clinically practicing mental health professionals, and explain how the Gioia-based analysis of these interviews will complement our framework. This research contributes to the literature on crises and consumption by exploring how financial resource scarcity may shape consumer lifestyles over time.
Proceedings of the European Marketing Academy : EMAC 2025 Spring Conference